1987
DOI: 10.1111/j.1471-4159.1987.tb01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of [3H]Ro 5–4864 and [3H]PK 11195 to Cerebral Cortex and Peripheral Tissues of Various Species: Species Differences and Heterogeneity in Peripheral Benzodiazepine Binding Sites

Abstract: The binding of [3H]PK 11195 and [3H]Ro 5-4864 to membrane preparations from cerebral cortex and peripheral tissues of various species was studied. [3H]PK 11195 (0.05-10 nM) bound with high affinity to rat and calf cerebral cortical and kidney membranes. [3H]Ro 5-4864 (0.05-30 nM) also successfully labeled rat cerebral cortical and kidney membranes, but in calf cerebral cortical and kidney membranes, its binding capacity was only 3 and 4%, respectively, of that of [3H]PK 11195. Displacement studies showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(43 citation statements)
references
References 22 publications
6
35
1
1
Order By: Relevance
“…I n c o n t r a s t t o a o r t a , a h i g h l y significant enhancement in the B max o f T S P O ( + 4 1 % ) determined with [ 3 H]PK 11195 binding was observed in testis tissue due to the HFHC + DMBA treatment, compared to control (data not shown). This was similar to the effects seen with HFHC diet alone and DMBA treatment alone (Dimitrova-Shumkovska et al, 2010a,b,c (Awad & Gavish, 1987;Dimitrova-Shumkovska et al, 2010a,b). This implies also that all of these K d values were not affected by HFHC and DMBA exposure.…”
Section: Wwwintechopencomsupporting
confidence: 69%
See 2 more Smart Citations
“…I n c o n t r a s t t o a o r t a , a h i g h l y significant enhancement in the B max o f T S P O ( + 4 1 % ) determined with [ 3 H]PK 11195 binding was observed in testis tissue due to the HFHC + DMBA treatment, compared to control (data not shown). This was similar to the effects seen with HFHC diet alone and DMBA treatment alone (Dimitrova-Shumkovska et al, 2010a,b,c (Awad & Gavish, 1987;Dimitrova-Shumkovska et al, 2010a,b). This implies also that all of these K d values were not affected by HFHC and DMBA exposure.…”
Section: Wwwintechopencomsupporting
confidence: 69%
“…PK 11195 and Ro5-4864 compete with each other in binding experiments, suggesting overlapping but not necessarily identical binding sites. It has been suggested that they interact with two different conformations or domains of the mitochondrial TSPO (Awad & Gavish, 1987). Behavioral studies have demonstrated that Ro5-4864 possesses anxiogenic and convulsant properties, whereas PK 11195 has been found to be anxiolytic and anticonvulsant (Gavish et al, 1999).…”
Section: Tspo Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control and 18-kDa PBR mRNA knockout cells were dubbed EnKat and anti-18-kDa PBR cells, respectively. 5 Ci/mmol; NEN Life Science Products) were used for binding studies, as described previously (25). Cells were scraped from 90-mm 2 culture dishes, washed with phosphate-buffered saline, and centrifuged at 1200 ϫ g for 5 min.…”
Section: Stable Transfection Of Ma-10 Cellsmentioning
confidence: 99%
“…Maximal binding capacity (B max ) and equilibrium dissociation constant (K d ) of the binding of the TSPO-specific ligand [ 3 H]PK 11195 were determined in whole cell membrane homogenates from the liver, as previously described (Awad and Gavish 1987). Radioactivity was counted with a 1600CA Tri-Carb liquid scintillation analyzer (Packard, Meriden, CT, USA).…”
Section: Tspo Binding Characteristicsmentioning
confidence: 99%